“For I Am Nothing without You”: Fragmentariness and the Transformability of Archetypal Identity in David Rabe’s The Orphan - Siapatori, Katerina (FOCUS: Papers in English Literary and Cultural Studies, 2020)
In the fi eld of literary refashioning and adaptation studies, ancient Greek drama has constituted an inexhaustible source of inspiration for artistic creation and production. When it comes to drama and theatrical performance, David Rabe’s The Orphan, the third play in his Vietnam-themed tetralogy, falls precisely in this category, as it is a revised and “extensive transposition” (Hutcheon 7) of two classical works: Aeschylus’s The Oresteia, the only surviving Greek trilogy, as well as Euripides’s Iphigenia at Aulis. In adapting these tragedies, the playwright chooses to juxtapose them onstage in order to represent and record the events which mark the generational trauma and the familial war in Agamemnon’s House. Rabe’s turn to classical Greek tragedy and his vision to rely on it and inform it are two inescapably “political acts” (Sanders 97), spurred by personal experience. The playwright had attended a performance of Euripides’s tragedy and had seen in it a link between the Trojan and the Vietnam War—and by extension Iphigenia’s sacrifice and the My Lai massacre—before proceeding, subsequently, to write the play in question. His realization that “the Greeks saw that reason was the flip side or dark side of unreason” and that his novel ideas were actually rooted in the ancient past (Morphos and Rabe 81) is the drive which urges him to base his play essentially upon the parent texts while attaching it to a uniquely different trajectory.